THE EFFECT OF SMOKING BEHAVIOR ON THE QUALITY OF LIFE AMONG FINAL YEAR STUDENTS BY USING PRECEDE MODEL IN SARI MUTIARA INDONESIA UNIVERSITY, INDONESIA - Hana Ike Dameria Purba; Mondha Kengganpanich; Sarunya Benjakul (Universitas Airlangga, 2022)
Introduction: The quality of life (QoL) of university students is an important aspect of creating the next leader inthe future, developing strong human resources, and improving the quality of generation. Therefore it is importantto understand the factors involved in improving the QoL of university students. Methods: This study intended toexplore QoL among the final-year students and factors related to it in the University by applying the PRECEDEmodel through a cross-sectional study. A total sample size of 171 final-year students was drawn by usingproportional sampling and probability proportional to size (PPS) for program selection and selected samples fromeach study program by accidental technique. Data were collected using the self-administered questionnaire, andWHOQOL-BREF was used to measure the QoL. Result: Data were analyzed by univariate and bivariate. Theoverall QoL was moderated (59.6%). There was a significant association between the availability of sellingcigarettes around the university and QoL (p=0.019), ease to buy cigarettes, and QoL (p= 0.038). Enabling factorsespecially had a direct impact on the QoL. Conclusion: Providing regulations related to smoking to the academiccommunity, giving moral responsibility to lecturers, and controlling the selling of cigarettes around the universitywould help increase the QoL.